Spatial Structure Remodeling in Yangtze River Delta Region Under High-speed Railway Network Organization - Yishuai Zhang (Journal of Regional and City Planning, 2019)
In recent years, China's high-speed railway construction has developed rapidly, playing an extremely important role in the exchange of elements between cities and supporting the operation of the national urban system. The Yangtze River Delta region is one of the most advanced and balanced regions in China. With the rapid development of China's high-speed railway construction, its regional spatial structure supported by the high-speed railway network has also undergone a series of changes. Based on the data of high-speed trains in the Yangtze River Delta region collected from the official website of the Ministry of Railways, the OD connection matrix between cities in the Yangtze River Delta was constructed, using some indexes such as network correlation degree, network density, central degree, to describe the characteristics of the city network in this region. The results show that, firstly, under the lead of Shanghai, the core corridor in the Yangtze River Delta region has been further strengthened. Secondly, as an important network hub in this region, the regional network status of Nanjing even exceeds that of Shanghai, and cities such as Hangzhou and Hefei also have the function of organizing sub-regional traffic. What is more, under the influence of the high-speed railway, the reach range of the metropolitan area has been greatly improved. A case comparison with the Ring-Bohai and Guangdong-Guangxi area showed that the Yangtze River Delta area is the most balanced among those three. Finally, some prospects for the future development of the Yangtze River Delta are discussed in this paper. Abstrak. Dalam beberapa tahun terakhir, pembangunan jaringab kereta api berkecepatan tinggi di Cina telah berkembang pesat, memainkan peran yang sangat penting dalam pertukaran elemen antara kota dan kota, dan mendukung sistem perkotaan nasional. Wilayah delta sungai Yangtze adalah salah satu daerah yang paling maju dan seimbang di Cina. Dengan perkembangan pesat pembangunan jaringan kereta api berkecepatan tinggi Cina, struktur tata ruang regionalnya yang didukung oleh jaringan kereta api berkecepatan tinggi juga telah mengalami serangkaian perubahan. Berdasarkan data kereta api berkecepatan tinggi di daerah delta sungai Yangtze yang dikumpulkan dari situs resmi kementerian perkeretaapian, dibangun matriks sambungan OD antara kota-kota di delta Sungai Yangtze dengan menggunakan beberapa indeks seperti tingkat korelasi jaringan, kepadatan jaringan, tingkat pemusatan, untuk menggambarkan karakteristik jaringan kota di wilayah ini. Hasilnya menunjukkan bahwa, pertama, di bawah pimpinan Shanghai, koridor inti di wilayah delta Sungai Yangtze telah diperkuat lebih lanjut. Kedua, sebagai hub jaringan penting di wilayah ini, status jaringan regional Nanjing bahkan melebihi Shanghai, dan kota-kota seperti Hangzhou dan Hefei juga memiliki fungsi mengatur lalu lintas sub-regional. Terlebih lagi, dipengaruhi kereta api berkecepatan tinggi, jangkauan area metropolitan telah sangat ditingkatkan. Perbandingan kasus dengan daerah Ring-Bohai dan Guangdong-Guangxi juga menunjukkan bahwa daerah delta Sungai Yangtze adalah yang paling seimbang di antara ketiga wilayah tersebut. Akhirnya, beberapa diskusi dan prospek tentang perkembangan masa depan delta sungai Yangtze disampaikan dalam makalah ini. Kata Kunci. Delta sungai Yangtze, kereta api berkecepatan tinggi, jaringan kota.Kata Kunci. Delta sungai Yangtze, kereta api berkecepatan tinggi, jaringan kota.